2017
DOI: 10.1002/14651858.cd006466.pub6
|View full text |Cite
|
Sign up to set email alerts
|

Oral anticoagulation in people with cancer who have no therapeutic or prophylactic indication for anticoagulation

Abstract: The existing evidence does not show a mortality benefit from oral anticoagulation in people with cancer but suggests an increased risk for bleeding.Editorial note: this is a living systematic review. Living systematic reviews offer a new approach to review updating in which the review is continually updated, incorporating relevant new evidence, as it becomes available. Please refer to the Cochrane Database of Systematic Reviews for the current status of this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 116 publications
0
20
0
1
Order By: Relevance
“…In the attempt to interpret these findings correctly, the lack of data specifically referred to the site of cancer origin should be considered. Indeed, the need of further evidence specifically related to the cancer type and stage is acknowledged by the authors themselves when discussing their research implications [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the attempt to interpret these findings correctly, the lack of data specifically referred to the site of cancer origin should be considered. Indeed, the need of further evidence specifically related to the cancer type and stage is acknowledged by the authors themselves when discussing their research implications [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence analysis by Kahale et al [87] could not confirm any survival benefit from treatments with oral anticoagulant agents, VKA, or DOACs in cancer patients with no previous VTE, but they did confirm an increase of bleeding risk.…”
Section: Anticoagulation In the Absence Of Vte To Improve Survival Inmentioning
confidence: 91%
“…3,4 In addition, Cochrane meta-analysis reviews have shown that LMWH consistently reduces the occurrence of symptomatic VTE but likely increases major and minor bleeding in cancer patients. [5][6][7] Despite these findings, LMHW is not routinely recommended in current guideline because of the low incidence of VTE in unselected patients, potentially increased risk of bleeding, high cost, and inconvenience of injections. 8 To determine which patients would receive the most benefit from a preventive strategy, recent studies have used a risk-stratified approach to study the impact of thromboprophylaxis in higher risk VTE patients based on the Khorana score.…”
Section: Introductionmentioning
confidence: 99%
“…Several randomized controlled trials (RCTs) have demonstrated benefit for low molecular weight heparin (LMWH) thromboprophylaxis in ambulatory cancer patients . In addition, Cochrane meta‐analysis reviews have shown that LMWH consistently reduces the occurrence of symptomatic VTE but likely increases major and minor bleeding in cancer patients . Despite these findings, LMHW is not routinely recommended in current guideline because of the low incidence of VTE in unselected patients, potentially increased risk of bleeding, high cost, and inconvenience of injections …”
Section: Introductionmentioning
confidence: 99%